Transmedia journalism and media consumption of the millennial generation (2018)
The current media scenario, marked by technological and narrative changes, requires journalists to constantly bring themselves up to date in order to maintain the connection with their audience. This article presents transmedia storytelling as the best ally of journalism for the dissemination of facts. This communicative model grants a nature of expansion, multiplicity and depth to the stories, which allows to raise the level of participation of the public in each medium in which information is developed.Specifically, this research seeks to detect the ways in which journalism can use transmedia narrative to reach and generate interaction in the millennial generation. To achieve this goal, a larger study that analyzes the consumption of resources made by young people in the region of Piura, in Peru, specifically, students in 5th year of secondary school in private schools in the area, was taken as a starting point.Thanks to the study, it was found that Piura students consume high, almost massive, amounts of digital media, especially social networks. In addition, they rely heavily on mobile devices as a gateway to the content offered on these platforms. Thus, news stories must be present in these media with attractive content in substance and form, that can satisfy this reader / viewer / millennial user who highly values quality content.